Environmental monitoring using plant test objects - Pazniak, Siarhei S. (Journal of the Belarusian State University. Ecology, 2019)
The issues of transformation of the species and chemical composition of segetal, ruderal and natural plant communities in the area of the impact of thermal power plants are studied. The dynamic trends occurring in the segetal flora are revealed, and the possibility of using plants as test for assessing the degree of contamination of phytocenoses with heavy metals is shown.
Keywords: segetal plants; biological diversity; agricultural crops; phytocenosis; agroecosystem; distribution monitoring and forecast; heavy metals